Monitoring geosites: a geoconservation tool at Azores Geopark - Lima, A. (2012)
The Azores archipelago is located in the North Atlantic and is composed by nine islands and some islets. This archipelago, and the surrounding seafloor, has a remarkable geological heritage of international scientific relevance, which constitutes the basis for the establishment of a geopark that is under evaluation by the European Geoparks Network (EGN). The analysis of the evolution of the conservation status of a geosite plays a very important role in the control of its decline. The decrease of relevance of a geosite could be justified either by direct degradation of a geological feature or by lack of concern in the maintenance of the site by local authorities.